(untitled) (Jurnal Arsitektur ARCADE, 2026)
Sustainable architecture plays a crucial role in minimizing environmental impact and enhancing energy efficiency in buildings. This study aims to explore research trends in sustainable architecture, particularly in housing, thermal comfort, and façade design, using bibliometric analysis with VOSviewer. The data were retrieved from the leading academic databases (Scopus). The analysis was conducted on the study maps keyword relationships, author collaborations, and institutional influences through co-occurrence network. The findings highlighted a growing emphasis on passive design strategies, innovative façade technologies, and adaptive thermal comfort models to promote sustainability in housing. Further analysis identified the cluster key themes involved thermal comfort, housing, architectural design, energy efficiency, and thermal insulation. This research offers valuable insights to develop the sustainable architecture, providing a useful reference for architects, policymakers, and researchers looking to enchance energi-efficient housing designs yet still prioritizing occupant comfort.